2018
DOI: 10.21089/njhs.32.0046
|View full text |Cite
|
Sign up to set email alerts
|

Pinworm (Enterobius vermicularis) Infection among Primary Level Government School Children of Chhampi, Lalitpur District, Nepal

Abstract: Introduction: Poor sanitation and crowding effect are easy way for transmission of enterobiasis between infected and uninfected person and it is usually common among playgroup and school kids.Subject and Methods: Among the various health problem of school children, enterobiasis is one of them still present among the school children in context of Nepal. Unawareness along with unhygienic lifestyle as well as crowdy environment may be the major reasons behind this. This study was aimed to find enterobiasis of sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other complaints were cough, anemia, itching, urticaria, vomiting, bloody diarrhea, and diarrhea in percentage of 7.41%, 18.52%, 9.26%, 3.7%, 7.4%, 3.7%, and 12.9%, respectively. 8 Mehraj et al reported that helminthiasis is endemic Worldwide. Humid and hot tropical climate, lack of access to potable water, poor hygiene, illiteracy, and poverty are the major risk factor for intestinal worm infections.…”
Section: Prevalence Of Sths Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other complaints were cough, anemia, itching, urticaria, vomiting, bloody diarrhea, and diarrhea in percentage of 7.41%, 18.52%, 9.26%, 3.7%, 7.4%, 3.7%, and 12.9%, respectively. 8 Mehraj et al reported that helminthiasis is endemic Worldwide. Humid and hot tropical climate, lack of access to potable water, poor hygiene, illiteracy, and poverty are the major risk factor for intestinal worm infections.…”
Section: Prevalence Of Sths Infectionsmentioning
confidence: 99%
“…7 In children, its rate is high due to soil transmission and nail biting. 8 According to the World Health Organization (WHO) estimates, 870 million children live in the area of high prevalence. The most affected regions of the world include Africa, South Asia, and South America.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterobiasis is caused by the intestinal nematode Enterobius vermicularis (E. vermicularis). 1 This type of worm is often reported to infect children, 2,3 but its prevalence in adults cannot be denied. 4 The incidence is quite variable in various regions, with the highest reported cases in Palestine at 98.9%.…”
Section: Introductionmentioning
confidence: 99%